2010
DOI: 10.1136/thx.2009.133751
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer screening and smoking abstinence: 2 year follow-up data from the Dutch-Belgian randomised controlled lung cancer screening trial

Abstract: Background Lung cancer screening may provide a new opportunity for attempts to quit among smokers or might delay smoking cessation, but studies to date failed to provide evidence for this. This study investigated the effect of lung cancer screening on smoking abstinence in male smokers participating in the DutcheBelgian randomised controlled lung cancer screening trial (NELSON trial). Methods In the NELSON trial, 50-to 75-year-old participants at high risk for developing lung cancer were randomised to either l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(136 citation statements)
references
References 25 publications
(45 reference statements)
5
124
1
6
Order By: Relevance
“…We did not take into account that participants in CT screening have higher cessation rates than nonparticipants (40). Thus, the introduction of a CT screening program could have a quantifiable and late effect on both lung cancer and all-cause mortality through a reduction in smoking prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…We did not take into account that participants in CT screening have higher cessation rates than nonparticipants (40). Thus, the introduction of a CT screening program could have a quantifiable and late effect on both lung cancer and all-cause mortality through a reduction in smoking prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Yapılan çalışmalarda, hastaların önemli kısmının malignite riski nedeni ile sigarayı bıraktığı saptanmıştır. 8,9 Çalışmamızda, pulmoner nodül izlemi yapılan hastaların cinsiyet, eğitim ve meslek gibi durumlardan bağımsız olarak yarıya yakının sigarayı bıraktığı belirlenmiştir. van der Aalst ve ark.nın çalışmasında, standart broşür ve anketlerle sigara içen hastalarda kanser taraması yapılan ve yapılmayan kontrol grubu karşılaştırıldığında; kanser taraması yapılan grupta sigara bırakma oranı istatistiksel olarak anlamlı düzeyde yüksek bulunmuştur.…”
Section: Discussionunclassified
“…van der Aalst ve ark.nın çalışmasında, standart broşür ve anketlerle sigara içen hastalarda kanser taraması yapılan ve yapılmayan kontrol grubu karşılaştırıldığında; kanser taraması yapılan grupta sigara bırakma oranı istatistiksel olarak anlamlı düzeyde yüksek bulunmuştur. 9 Argüder ve ark.nın yaptığı çalışmada, hastaların yarısının ileride sağlığının bozulma korkusu nedeni ile sigarayı bırakmak istediği belirlenmiştir. 8 Çalışmamızda, nodülün malignite riski anlatılan hastaların, Argüder ve ark.nın yaptığı çalışmaya paralel olarak %48 oranında sigarayı bıraktığı saptanmıştır.…”
Section: Discussionunclassified
“…Data from the NELSON study showed those in the screened and control arms had higher rates of smoking cessation than the background population, suggesting those motivated to participate in the trials may be amenable to health promotion. 12 Studies have also shown that smoking abstinence was increased in those with indeterminate and positive results compared with those with negative results, suggesting fear of a cancer diagnosis may motivate quit attempts. 13 It is therefore imperative in those with normal scans to balance reassurance with the promotion of health-protective behaviours.…”
Section: Smoking Cessation Vitalmentioning
confidence: 99%